Characteristics of Monitoring of Practice-Oriented Competences of Future Educational Psychologist in Russian University - V. Vardanyan, Y.; V. Vardanyan, L.; Ð. Vdovina, N.; P. Kondratyeva, N.; V. Sergunina, S.; V. Fadeeva, O. (International Journal of Engineering and Technology, 2018)
Introduction. The paper rationalizes the urgency of creating a modern university monitoring model which analyses the development of practice-oriented competences of a future educational psychologist. The construction of practice-oriented competences on an interdisciplinary competence basis is fast becoming a key instrument in education. Of much importance is the strategy when the integrated organization of comprehensive monitoring procedures emerges from scientific and methodological resources. The review of modern ideas plays a pivotal role in our research. We describe the modern university monitoring model as a system of assessment and control procedures ensuring the psychic professional and personal developments of future educational psychologist. Practice-oriented competences play a critical role in future effective professional activity. The purpose of the paper is to characterize the structure and content of the practice-oriented competences of future educational psychologist, to justify and reveal the model of monitoring competencesâ€™ development with the help of the example of a Russian university.Materials and methods. Data were collected using the monitoring models that function in modern practices of Russian universities. The study began with the qualitative review of specific scientific literature devoted to the problem of practice-oriented competences of educational psychologist. The main method is analytical description. We rated various experiences of assessing the competencesâ€™ development describing the design of their structure and content, as well as justifying the model of their monitoring in Russian universities.Results. In our research we provide much suggestive evidence to substantiate the list of practice-oriented competences of future educational psychologist. Our interesting findings are the structure and the content of the competences under analysis. The most meaningful finding is a modern theoretical monitoring model which is critical for an insightful analysis of practice-oriented competences, as well as the scientific and methodological resources of its implementation in Russian universities. One of the most significant achievements to emerge from the study is the set of evaluation tools and monitoring procedures which ensures its successful approbation in one of Russian universities.Discussion. Multiple analysis revealed that the adequacy of assessing practice-oriented competences of the future educational psychologist emerges from a set of sufficient evaluation tools. The present study identified that the monitoring procedures allow to describe step-by-step the state of the competencies under analysis, as well as their dynamics. Overall, the study strengthens the idea of improving the monitoring system of practice-oriented competencesâ€™ development in Russian universities. The study also outlines the prospects of the monitoring systemâ€™s implementation.Conclusion. The following conclusions can be drawn from the present study. To prepare skilled educational psychologist with high professional qualification it is critical to develop the set of tasks to identify the list of practice-oriented competences. The structure and content of the tasks, as well as the development of assessment tools play a crucial role in a stage-by-stage application of monitoring procedures in Russian universities. The findings will be of interest for professionals who are open to innovation and development.Â